2014
DOI: 10.1093/geronb/gbt165
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity and Psychological Health As Mediators of the Relationship Between Physical Health and Marital Quality

Abstract: The results suggest ways to protect marital quality among older adults who are struggling with physical illness in themselves or their partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 54 publications
(72 reference statements)
4
103
0
5
Order By: Relevance
“…The present findings were agreed with (20) who develop a conceptual model that links married older adults physical health and that of their spouse to positive and negative dimensions of marital quality via psychological well-being of both partners and their sexual activity and reported that sexual activity mediates the association between own and partner's physical health and positive marital quality. This could be explained as sexual and marital satisfactions are equally tied together for men and women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present findings were agreed with (20) who develop a conceptual model that links married older adults physical health and that of their spouse to positive and negative dimensions of marital quality via psychological well-being of both partners and their sexual activity and reported that sexual activity mediates the association between own and partner's physical health and positive marital quality. This could be explained as sexual and marital satisfactions are equally tied together for men and women.…”
Section: Discussionsupporting
confidence: 91%
“…The questionnaire evaluated 20 items in three domains: predisposing factors (13 items), enabling factors (4 items), and reinforcing factors (3 items). In the domain of predisposing factors, knowledge (6 items) was evaluated on the basis of yes/no/don't know questions (possible score 6-18), and attitudes, beliefs, and values (7 items) were evaluated using a three-point Likert scale (from agree = 3, uncertain = 2, and disagree = 1, possible score (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The researcher considers negative attitude if total score was less than 14 while, positive attitude, if the total score more than 14.…”
Section: IIImentioning
confidence: 99%
“…Moreover, health problems of older adults may interfere with their desire for or ability to engage in sexual activities, such as sexual touching and intercourse (Karraker et al, 2011). The link between physical health and sexual activity may explain the observed association between increased age and decreased engagement in partnered sexual activity (Call, Sprecher, & Schwartz, 1995;Galinsky & Waite, 2014). Furthermore, a given health condition may have a different effect on sexual function for older men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that communication skills could reduce marital discord and conflicts whereas the growth of such conflicts would end in disinterest and disrespect towards a spouse (Tavakkolzadeh, Negatian & Soori 2015;Stanley, 2003;Gottman, 2004;Cohen, 2005; quoted by Hossein Khan Zadeh & Yeganeh, 2013). Reducing such conflicts, on the other hand, would decrease mental health problems (Galinsky & Waite, 2014), depression (Wang, Wang, & Miller, 2014), and impaired sexual function (Metz & Epstein, 2002).…”
Section: Discussionmentioning
confidence: 99%